The Relationship Between Life Satisfaction of the School of Physical Education and Sports Students and Their Levels of Sports Engagement - Hande İnan and Mine Koç (Journal of Educational Issues, 2024)
This study aims to investigate the correlations between the life satisfaction of students of study sport sciences and their levels of sports engagement according to a number of variables. The study group was composed of 116 undergraduate students attending the School of Physical Education and Sport of Adıyaman University. The participants were administered “Sports Engagement Scale (SES)” and “Satisfaction with Life Scale (SWLS)” in addition to a personal information form prepared by the researcher. The data collected were analysed on SPSS statistics programme and 0.01-0.05 significance level was accepted for the statistical validity of the data. Weak and positive correlations were found between physical education and sport school students’ life satisfaction with life and their sports engagement. In addition to that, weak and negative correlations were found between the participants’ grade point averages and their scores of sports engagement. The female students’ grade point averages were significantly higher than the male students’. In conclusion, university students’ sports engagement results in more satisfaction with life. The increase in sports engagement and life satisfaction of university students causes a decrease in their academic success.